Patients with chronic mild or moderate traumatic brain injury have abnormal brain enlargement. (2nd January 2020) - Ross, David E.; Seabaugh, John D.; Seabaugh, Jan M.; Alvarez, Claudia; Ellis, Laura Peyton; Powell, Christopher; Hall, Christopher; Reese, Christopher; Cooper, Leah; Ochs, Alfred L.
ABSTRACT: Introduction: Much less is known about brain volume abnormalities in patients with chronic mild or moderate traumatic brain injury (TBI) compared with patients with more severe injury. Commercially available software methods including NeuroQuant® are being used increasingly to assess MRI brain volume in patients with TBI. Methods: 50 patients with mild or moderate TBI were compared to the NeuroQuant® normal control database ( n = thousands) with respect to MRI brain volume. Results: The patients had many areas of abnormal enlargement and fewer areas of atrophy, including abnormally small cerebral white matter (CWM) limited to the first 10 months after injury. Examination of correlations within the patient group between CWM volume and volumes of the abnormally enlarged regions showed multiple significant negative correlations, indicating that CWM atrophy correlated with enlargement of the other regions. Discussion: The finding of many regions of abnormal brain enlargement was relatively new, although a couple of previous studies of patients with mild TBI found similar but more limited findings. The cause of the abnormal enlargement was unknown, but possibilities included: (1) hyperactivity and hypertrophy; or (2) chronic neuro-inflammation and edema. Abbreviations: ADNI: Alzheimer's Disease Neuroimaging Initiative; CWM: cerebral white matter; GM: cerebral cortical gray matter; ICC: intraclass correlations coefficient; IFT: infratentorial; MRI: magnetic resonance imaging; mTBI: mild TBI; NQ: NeuroQuant®; SCN: subcortical nuclei; t0: time of injury; t1: time of first NeuroQuanted MRI scan after injury; t2: time of second NeuroQuanted MRI scan after injury; TBI: traumatic brain injury; VBR: ventricle-to-brain ratio; WBP: whole-brain parenchyma.